PENGEMBANGAN PASAR DAN PROMOSI PEMASARAN MELALUI MEDIA ONLINE BAGI UKM PERMATA KOPI DESA PASIR ANGIN KECAMATAN DARANGDAN - Jejen Jaenudin; Indra Maulana; Neni Faridoh (Universitas Mercu Buana, 2022)
Micro, Small, and Medium Enterprises must have competitiveness in order to survive. One strategy to increase competitiveness is to use the right marketing media that combines offline (conventional) and online marketing media. The marketing media owned by Permata Coffee Micro, Small, and Medium Enterprises were previously still conventional, namely offline, so market growth was also very slow. This community service aims to help Permata Coffee complete its promotional media with online promotional media to expand its market share and accelerate its growth. The stages carried out are analysis of e-commerce platforms, registration, training, and assistance in using e-commerce platforms, as well as monitoring and recapitulation of sales results through the e-commerce platforms. As a result of carrying out this activity, Permata Coffe already has an official account on social media and a shop on the e-commerce platform. Permata Coffee has also been able to increase its coffee sales by selling to several cafes in Purwakarta. Keywords: marketing media; e-commerce platforms; promotion; Micro small and Medium Enterprises